PERAN INDUSTRIALISASI PEDESAAN DALAM MENINGKATKAN PEREKONOMIAN MASYARAKAT DESA BARUGA KECAMATAN UEPI KABUPATEN KONAWE SULAWESI TENGGARA - Marsel Kristian Cahyadi; Jamaluddin Hos (Journal Publicuho, 2025)
This study aims to analyse the role of rural industrialisation in improving the local economy of Baruga Village, Uepi Sub-district, Konawe Regency. The main research question is: to what extent does the rural industrialisation program affect household income and the village's economic structure? This research employed a mixed-methods approach with a sequential explanatory design. Quantitative data were collected through surveys of 150 respondents, while qualitative data were obtained via in-depth interviews, focus group discussions, and participatory observation. The findings reveal that the industrialisation program, initiated in 2020, increased average household income by 37.8%, promoted income diversification, and transformed the village economy from a primary sector orientation to a more balanced structure, including the secondary sector. Positive economic impacts also include new employment opportunities and growth in local processing industries. These results emphasise that participatory approaches and the utilisation of local resources are key to the success of rural industrialisation. The implications underline the importance of strengthening infrastructure, developing human resource capacity, expanding access to capital, and integrating village-level institutions. This study contributes empirically to the development of local economic development theory based on rural industrialisation and provides policy direction for similar programs in other regions.